WEB-BASED INFORMATION SYSTEM FOR PROPERTY LOSS ADJUSTER REPORT MANAGEMENT IN PT.XYZ - Faradila Athaya Wardhani; Genta Sahuri (President University, 2021)
Abstract—PT. XYZ is one of the independentlossAdjusterinIndonesia,whichhelpinsurancecompanies to assess the client losses in the field ofproperty. As an independent loss Adjuster company,PT XYZ is responsible for aiding insurance agencies ingatheringdatarelatingtolossassessmentsandestimatingtheleveloflosssustained.Areportmanagementsystemisrequiredtoassisttheorganizationalprocessfromreportingtoreportcollection due to the short processing time limit and thelarge amount of data produced by each project. ThisthesiswillcovertheestablishmentofaReportManagementSystemtomanageandmonitortheproject and creating the assessment report for eachproject in compliance with PT.XYZ standards. As aresult,thepossibilityofmisplaceddocumentsisreduced, the compilation of an assessment report isaccelerated, and also the execution of each task can bewell controlled.